1992
DOI: 10.1902/jop.1992.63.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators for Periodontitis in a Military Treatment Population

Abstract: The association between the periodontal diagnosis and a variety of subject characteristics was studied in a group of 1,783 patients examined at a large military dental clinic. In order of importance, age greater than 30, smoking, male sex, and Filipino racial background were all found to be statistically significant risk indicators for the presence of moderate or advanced periodontitis. A logistic regression equation serving as a predictive model employing these four variables was presented. The strong associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(60 citation statements)
references
References 19 publications
9
49
0
2
Order By: Relevance
“…The strong association found between smoking and advanced periodontal diseased is consistent with the hypothesis that smoking has cumulative detrimental effects on periodontal health (Horning et al, 1992) thus there is good evidence that the more a patient smokes the greater the degree of periodontal disease. In this study results has shown that current smokers represent a mean duration of 15 years while former smokers represent 21 years.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The strong association found between smoking and advanced periodontal diseased is consistent with the hypothesis that smoking has cumulative detrimental effects on periodontal health (Horning et al, 1992) thus there is good evidence that the more a patient smokes the greater the degree of periodontal disease. In this study results has shown that current smokers represent a mean duration of 15 years while former smokers represent 21 years.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, former smokers were 1.68 times more likely to suffer from periodontitis (Tomar and Asma, 2000). Horning et al (1992) reported an association between smoking and advanced periodontitis. This is consistent with the hypothesis that smoking has a cumulative effect on periodontal health i.e., the more a patient smokes, the greater the degree of chronic inflammatory periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…17 Horn ing's study in 1992 found similar results, reporting males to have increased risk of moderate or advanced periodontitis (OR 1.78, 95% CI: 1.42-2.46). 20 Male gender deserves consideration in a risk model for periodontal disease, the effects of which must be addressed through behaviour modifi cation.…”
Section: Gendermentioning
confidence: 99%
“…Cross-sectional and longitudinal studies have detailed the consistent, positive association between smoking and periodontal attachment loss (Bergstrom 1989, Preber & Bergstrom 1990, Haber & Kent 1992, Horning et al 1992, Haber et al 1993, Ah et al 1994. A meta-analysis of the literature conducted by Papapanou (1996) for the 1996 World Workshop in Periodontics revealed that smokers have an almost 3-fold increase in their risk for severe periodontal disease vs non-smokers.…”
Section: Introductionmentioning
confidence: 99%